The alternation in higher education: challenges and perspectives in the Degree in Rural Education/UFV - Sthefani Loti Paiva Lima; Lourdes Helena da Silva (Universidade Federal do Norte do Tocantins, 2020)
In the last decades, in our society, the experiences of alternating training are expanding and the most recent phenomenon of this pedagogical practice is found in the scope of Higher Education. Studies in the specific context of the training experiences of educators in the field reveal that the alternation in these courses is a process under construction and point out the need for new academic works that can contribute to a better understanding of the course of different degrees in Rural Education. It is in this context that the present article is inserted, whose purpose is to describe and analyze the construction of alternation in the Degree in Rural Education at the Federal University of Viçosa. In methodological terms, the data were obtained from the combination of documentary research, participant observation and interviews with eight professors of the course. In our analyzes, we seek to present some reflections on teaching practice that could contribute both to subsidize actions and strategies of the course and to advance in the understanding of the possibilities of alternating training in Higher Education, analyzing the challenges experienced in the consolidation of this educational experience.